PENGEMBANGAN BAHAN AJAR HIMPUNAN MATEMATIKA YANG DIKAITKAN DENGAN NILAI-NILAI ISLAM - Umi Khoiriyah; Swaditya Rizki (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The objective of this research is to develop teaching materials of mathematical set based on Islamic values that are feasible, practical, and effective. This research type is Research and Development (R&D). The model used in this research is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The instruments of data collection used the questionnaires and evaluation questions. The result of this research is the average of expert validation is 81,48% (very feasible). Then, based on the implementation of the student small group is obtained practicality percentage of 82%. While the result of the field trial in one class is obtained effectiveness percentage of 66,67%. Therefore, this research can be concluded that teaching materials of mathematical set based on Islamic values are feasible, practical, and effective.